Regulation of magnetocaloric properties and critical behavior of La0.7Sr0.3MnO3 by high-pressure heat treatment - Xiang Jin; Huaijin Ma; Qi Li; Jiawei Xu; Jianjun Zhao; Tegus O; Jiaohong Huang (iScience)
Summary: La0.7Sr0.3MnO3 polycrystalline samples were prepared using a two-step process (high-temperature solid-phase reaction method and high-pressure heat treatment) under different pressures. The magnetocaloric properties of the samples exhibited a significant dependence on pressure. The nonlinear changes in average bond length with pressure were defined in two stages: 0–2 GPa (S1) and 2-4-6 GPa(S2). S1: The double-exchange interaction was weakened and the Curie temperature was decreased from 367 K to 338 K due to negative volume compressibility, while the peaks of magnetic entropy change were reduced. S2: The rate of linear increase in Curie temperature induced by normal cell contraction is 5.6 K·GPa−1. Maximum magnetic entropy change and refrigeration temperature span varied at the rates of 0.29 J·kg−1·K−1·GPa−1 and -5.37 K·GPa−1, respectively. All the samples exhibited a second-order ferromagnetic-paramagnetic transitions with critical behavior evolving from mean-field model adherence (S1) to deviation (S2). The magnetocaloric properties of La0.7Sr0.3MnO3 can be effectively regulated by pressure.